PHOTOVOLTAIC MODELING METHODS BASED ON MATLAB SIMULINK IMPLEMENTATION - Azriyenni Azhari Zakri; Nurhalim Nurhalim; Dohardo P.H. Simanulang; Ihwallibi Tribowo (Universitas Mercu Buana, 2018)
This paper presents photovoltaic system as a stand-alone electric power plant in the renewable energy development. To maximize these stand-alone generators, it is necessary to design photovoltaic modeling to produce energy and maximum power. The problems that exist in the design of PV systems are PV configuration, battery size, and the maximum power system. Therefore, this research will be proposed modeling Matlab/Simulink based PV system. The contribution of this research can provide various characteristics of the photovoltaic system with a capacity of 100 Wp. This modeling is designed using Matlab/Simulink software. The data generated from this simulation will provide a good reference for designing the stand-alone generators in the future.